Teachers as Motivators and Facilitators: A Qualitative Study on Enhancing Students’ Learning Outcomes in History Education - Anggita, Mei Shinta; Rohmawati, Rina; Wijaya, Agi Ma'ruf (Journal Of Educational Experts (JEE), 2026)
This study aims to examine how teachers’ roles as motivators and facilitators are enacted to improve students’ learning outcomes in history education at the secondary level. Despite extensive literature on motivational teaching or facilitative pedagogy, integrated analyses of both roles within history learning contexts remain limited. This research contributes a motivational–facilitative pedagogical construct that conceptualizes the synergy between affective encouragement and student-centered facilitation. Empirical evidence indicates that consistent motivational reinforcement and facilitative classroom practices were associated with observable improvements in students’ engagement, participation, and learning discipline. Employing a qualitative multi-case study design, this research was conducted in a vocational secondary school context. Data were collected through non-participant observation, semi-structured interviews, and document analysis. The study involved eight informants, consisting of one principal, one vice principal for curriculum, two history teachers, and four students. Data analysis followed Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing, with source and technique triangulation ensuring data credibility. The findings reveal three key results: (1) teachers’ motivational strategies strengthened students’ learning persistence and classroom discipline; (2) facilitative practices fostered critical thinking, confidence, and active participation; and (3) the integration of both roles created a supportive learning climate that significantly enhanced history learning outcomes.